ANALYSIS OF STANDARD OPERATING PROCEDURES, SERVICE INNOVATION, AND EMPLOYEE PROFESSIONALISM ON PUBLIC SATISFACTION WITH SERVICE ACCESSIBILITY AS AN INTERVENING VARIABLE INTERVENING IN THE POPULATION AND CIVIL REGISTRATION OFFICE OF CIVIL REGISTRATION OFFI - Lasma Uli Simangunsong; Nurafrina Siregar; Muhammad Dharma Tuah Putra Nasution (RADJA PUBLIKA, 2025)
Population administration services require speed, accuracy, transparency, and ease of access. This study analyzes the influence of Standard Operating Procedures (SOPs), service innovation, and employee professionalism on public satisfaction, with service accessibility as an intervening variable at the Population and Civil Registration Office of Medan City. The research design is a quantitative cross-sectional study using a survey of 96 respondents (Cochran's sample size determination technique). The analysis was conducted using PLS-SEM (SmartPLS). All indicators met convergent validity (outer loading ≥ 0.70) and reliability (Composite Reliability 0.935–0.961; AVE 0.705–0.830). The model had high explanatory power: R² accessibility = 0.864 and R² satisfaction = 0.837. Path testing results showed: SOP → accessibility was positive and significant (β=0.225; p=0.031), but SOP → satisfaction was not significant (β=−0.056; p=0.673); innovation → significant accessibility (β=0.544; p<0.001) and innovation → significant satisfaction (β=0.322; p=0.049); professionalism → significant accessibility (β=0.205; p=0.047) while professionalism → satisfaction was not significant (β=0.221; p=0.118); accessibility → significant satisfaction (β=0.460; p=0.041). The mediation test showed significant mediation in the path of innovation → accessibility → satisfaction (β=0.250; p=0.048), while the mediation of SOP and professionalism through accessibility was not significant. The findings confirm that improving accessibility—driven primarily by service innovation—is key to increasing public satisfaction. Practical implications recommend strengthening needs-based innovation (e.g., online queuing and tracking, mobile services), enforcing SOPs for process consistency, and monitoring digital performance to maintain service accountability.